Ethnicity as Desire: Post-Colonial Gay Pornographic Film in Europe - Busse, Emre (Queer Futures, 2024)
What can ethnic differences tell us about the desiring gaze while addressing the motives that result from the power and desire in gay ethnic pornography in Europe? How do pornographic films authenticate their ethnic subject in different European countries and how can the fetishism of presenting an authentically foreign body be best approached? Is the transformation of sex tourism, which affects countries differently, reflected through the ever-evolving history of gay pornography in Europe? And how does this transformation contrast or overlap with the legacies of Orientalism and colonialism? In addressing these questions, this book will participate in ongoing debates concerning Orientalism and colonialism, and make a contribution to the growing field of pornography studies. While recent works by scholars have considered the relation between US mainstream gay pornography and its representations of ethnicity and ‘race,’ and have also discussed examples from Europe (predominantly France), no historical study has yet bridged the gap between earlier European gay ethnic pornography and its current, specifically German-Turkish manifestations. Furthermore, this exploration of recent studios like GayHeim will also contribute to discussions on the mobility issues of non-European men, while illustrating how these new productions can be refugee—or migrant—positive while simultaneously perpetuating Orientalism.